2003
DOI: 10.1096/fj.03-0178fje
|View full text |Cite
|
Sign up to set email alerts
|

NAADP activates a Ca2+current that is dependent on F‐actin cytoskeleton

Abstract: Nicotinic acid adenine dinucleotide phosphate (NAADP) is involved in the Ca2+ response observed at fertilization in several species, including starfish. In this study, we have employed Ca2+ imaging and the single-electrode voltage-clamp technique to investigate whether the NAADP-mediated Ca2+ entry discovered in our laboratory in starfish oocytes was underlain by a membrane current and whether the response to NAADP required an intact cytoskeleton. Uncaging of preinjected NAADP evoked a cortical Ca2+ flash that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 48 publications
3
49
0
Order By: Relevance
“…There has even been speculation about a physical link between lysosomally located NAAPD ϩ receptors and Ca 2ϩ channels in the plasma membrane (45) blocker. Similarly, in starfish oocytes, the Ca 2ϩ response was sensitive to thapsigargin (25), and thapsigargin also abolished the NAADP ϩ -stimulated secretion of insulin in human ␤-cells (34). The fact that no massive Ca 2ϩ release from the endoplasmic reticulum was detected after lysosomal disruption could be explained by the hypothesis that lysosomal activation by NAADP ϩ is a requirement for the subsequent activation of Ca 2ϩ release from thapsigargin-sensitive stores.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…There has even been speculation about a physical link between lysosomally located NAAPD ϩ receptors and Ca 2ϩ channels in the plasma membrane (45) blocker. Similarly, in starfish oocytes, the Ca 2ϩ response was sensitive to thapsigargin (25), and thapsigargin also abolished the NAADP ϩ -stimulated secretion of insulin in human ␤-cells (34). The fact that no massive Ca 2ϩ release from the endoplasmic reticulum was detected after lysosomal disruption could be explained by the hypothesis that lysosomal activation by NAADP ϩ is a requirement for the subsequent activation of Ca 2ϩ release from thapsigargin-sensitive stores.…”
Section: Discussionmentioning
confidence: 93%
“…Also in mature starfish oocytes, the amplitude of the response to NAADP ϩ could be strongly reduced by the L-type Ca 2ϩ channel blockers verapamil and nifedipine (27). Moreover, NAADP ϩ induced a Ca 2ϩ influx, as measured by the patch clamp technique, which could be significantly reduced by L-type Ca 2ϩ channel blockers (25). There has even been speculation about a physical link between lysosomally located NAAPD ϩ receptors and Ca 2ϩ channels in the plasma membrane (45) blocker.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Again, similar to the sea urchin egg, imaging of the Ca 2+ increase in response to NAADP reveals that NAADP-induced Ca 2+ release initiates in the cortex of matured oocyte (Lim et al, 2001). An inwardly rectifying Ca 2+ -selective membrane current activated by NAADP has recently been characterised (Moccia et al, 2003). This current is insensitive to a combination of heparin and 8-NH 2 -cADPR which (as discussed above) is sufficient to attenuate global Ca 2+ increases in response to NAADP (Santella et al, 2000).…”
Section: +mentioning
confidence: 98%
“…Hence, in starfish eggs, NAADP appeared to work on Ca 2+ channels at the plasma membrane [91]. NAADP also triggered the sperm-evoked initial depolarization (fertilization potential) in starfish eggs by the activation of a Ca 2+ -mediated inward current, which is mainly carried by Ca 2+ and displays an inwardly-rectifying I-V relationship [101,102]. Taken together, these results suggested that NAADP could recapitulate some of the early events induced by the fertilizing sperm.…”
Section: Roles Of Naadp and Insp 3 For The Ca 2+ Response At Fertilizmentioning
confidence: 99%